Testudo cf. graeca from the new Late Miocene locality of Platania (Drama basin, N. Greece) and a reappraisal of previously published specimens - Vlachos, E.; Tsoukala, E. (Bulletin of the Geological Society of Greece, 2014)
In this paper we describe a new Neogene mammalian site and one of the latest discoveries of a fossil tortoise in Greece, from Platania locality, in Drama basin, Northern Greece. The preliminary study of the numerous fossil mammal remains shows that the recovered fauna is of Late Miocene age. The tortoise material consists of a partial shell and a limb bone that belong to the same individual. They are attributed to the Testudo cf. graeca, and are members of the Testudo s.s. lineage, characterized by the presence of a hypo–xiphiplastral hinge. This new material indicates that the presence of T. graeca in Greece could expand into the Late Miocene. Comparisons with other fossils of the genus Testudo s.s. from Greece, allowed the revision of previously published specimens of T. graeca.